Fluoride exposure and blood cell markers of inflammation in children and adolescents in the United States: NHANES, 2013-2016 - Pamela Den Besten; Christine R. Wells; Dawud Abduweli Uyghurturk (BMC, 2022)
Abstract Background Ingestion of fluoride in drinking water has been shown to result in increased cellular markers of inflammation in rodent models. However, the approximately 5-10 × increase in water fluoride concentrations required in rat and mouse models to obtain plasma fluoride concentrations similar to those found in humans has made relevant comparisons of animal to human studies difficult to assess. As an increased white blood cell count (WBC) is a marker of inflammation in humans, we used available NHANES survey data to assess the associations between plasma fluoride levels in the U.S. and blood cell counts children and adolescents.   Methods Multiple linear regressions were done to determine the association of blood cell counts and plasma fluoride in publicly available NHANES survey data from the 2013-2014 and 2015-2016 cycles. Plasma fluoride concentration measurements were available only for children aged 6 to 19, inclusive, and therefore this subpopulation was used for all analyses. Covariate predictors along with plasma fluoride were age, ethnicity, gender, and Body Mass Index (BMI).  Results Plasma fluoride was significantly positively associated with water fluoride, total WBC count, segmented neutrophils, and monocytes, and negatively associated with red blood cell count when adjusted for age, gender and BMI. Conclusion Our finding that neutrophils and monocytes are associated with higher plasma fluoride in U.S. children and adolescents is consistent with animal data showing fluoride related effects of increased inflammation. These findings suggest the importance of further studies to assess potential mechanisms that are involved in absorption and filtration of ingested fluoride, particularly in tissues and organs such as the small intestine, liver and kidney.